TMAO influence on the backbone of proteins: an oligoglycine model - Hu, Char Y. (2010)
The study of organic osmolytes has been pivotal in demonstrating the role of solvent effects on the protein backbone in the folding process. Whereas a thermodynamic description of the interactions between the protein backbone and osmolyte has been well defined, the structural analysis of the effect of osmolyte on the protein backbone has been incomplete. Therefore, we have carried out simulations of a peptide backbone model, glycine(15) in protecting osmolyte TMAO solution in order to determine the effect of the solution structure on the conformation of the peptide backbone. We demonstrate that the models chosen show that the ensemble of backbone structures shifts towards a more collapsed state in TMAO solution as compared to pure water solution. The collapse is consistent with preferential exclusion of the osmolyte caused by unfavorable interactions between osmolyte and peptide backbone. The exclusion is due to strong triplet correlations of osmolyte, water, and peptide backbone. This provides a clear mechanism demonstrating that even a modest concentration of TMAO forces the protein backbone to adopt a more collapsed structure in the absence of sidechain effects.